I am simplifying rational expressions and I'm so confused how to simplify 2x-10 over x-5. Any help? Topic: Math 2 Answers | Add Yours cosinusix | College Teacher | (Level 3) Assistant Educator Posted on March 29, 2012 at 8:51 AM `(2x-10)/(x-5)=(2*x-2*5)/(x-5)=(2(x-5))/(x-5)=2 (x-5)/(x-5)=2` `(2x-10)/(x-5)=(2*x-2*5)/(x-5)=(2(x-5))/(x-5)=2 (x-5)/(x-5)=2` academy633 | College Teacher | (Level 1) Salutatorian Posted on March 29, 2012 at 8:11 AM (2x-10)/(x-5) = 2(x-5)/(x-5) = 2 We’ve answered 301,455 questions. We can answer yours, too. Ask a question

cosinusix | College Teacher | (Level 3) Assistant Educator Posted on March 29, 2012 at 8:51 AM `(2x-10)/(x-5)=(2*x-2*5)/(x-5)=(2(x-5))/(x-5)=2 (x-5)/(x-5)=2` `(2x-10)/(x-5)=(2*x-2*5)/(x-5)=(2(x-5))/(x-5)=2 (x-5)/(x-5)=2`

academy633 | College Teacher | (Level 1) Salutatorian Posted on March 29, 2012 at 8:11 AM (2x-10)/(x-5) = 2(x-5)/(x-5) = 2